Analisis Deiksis Dalam Novel Origami Hati Karya Boy Candra Dan Implikasinya Terhadap Pembelajaran Teks Cerita Pendek di SMP - Ocviarissa Rivera; Petrus Poerwadi; Albertus Purwaka; Paul Diman; Juniarti Juniarti; Yurika Yurika; Isti Prihatini (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
The aims of this study were (1) to describe the form of persona deixis in Boy Candra's novel Origami Hati, (2) to describe the form of place deixis in Boy Candra's Origami Hati novel, (3) to describe the form of time deixis in Boy Candra's Origami Hati novel, ( 4) to describe the function of persona deixis in the novel Origami Hati by Boy Candra, (5) to describe the function of deixis of place in the novel Origami Hati by Boy Candra, (6) to describe the function of time deixis in the novel Origami Hati by Boy Candra, (7) to describe the implications of deixis in the novel Origami Hati by Boy Candra on learning short story texts in junior high school. The results showed that the deixis contained in the novel Origami Hati by Boy Candra includes first-person deixis, second-person deixis, third-person deixis, place deixis and time deixis and their respective functions. The function of persona deixis in this novel is used to refer to actors or participants who are involved in language events; used as a pointer to belonging; used as a subject; used as an object. The function of place deixis in this novel is used as a description of the place where a language event takes place. The function of time deixis in this novel is used to refer to the time of utterance; used to refer to past or before utterances; used to refer to the time after the utterance. Personal deixis in this novel consists of the form aku, -ku, saya, anda, kami, kita, kamu, -mu, kalian, dia, -ia, mereka. The deixis of time in this novel refers to the past, present and future. The deixis of place in this novel refers to places that are far from the speakers, close to the speakers and somewhat far from the speakers.